Impact of a “Diagonal” Intervention on Uptake of Sexual and Reproductive Health Services by Female Sex Workers in Mozambique: A Mixed-Methods Implementation Study - Lafort, Yves; Lessitala, Faustino; Ismael de Melo, Malica Sofia; Griffin, Sally; Chersich, Matthew; Delva, Wim (Frontiers in Public Health, 2018)
Background Female sex workers (FSWs) have high risks for adverse sexual and reproductive health (SRH) outcomes, yet low access to services. Within an implementation research project enhancing uptake of SRH services by FSWs, we piloted a ‘diagonal’ intervention, which combined strengthening of FSW-targeted services (vertical) with making public health facilities more FSW-friendly (horizontal), and tested its effect. Methods The study applied a convergent parallel mixed-methods design to assess changes in access to SRH services. Results of structured interviews with FSWs pre-intervention (N=311) and thereafter (N=404) were compared with the findings of eight post-intervention focus group discussions (FGD) with FSWs and two with FSW-peer educators. Results Marked and statistically significant rises occurred in consistent condom use with all partners (from 55.3% to 67.7%), ever use of female condoms (37.9% to 54.5%), being tested for HIV in the past six months (56.0% to 76.6%), using contraception (84.5% to 95.4%), ever screened for cervical cancer (0.0% to 16.9%) and having ≥10 contacts with a peer educator in the past year (0.5% to 24.45%). Increases mostly resulted from FSW-targeted outreach, with no rise detected in utilization of public health facilities. FGD participants reported that some facilities had become more FSW-friendly, but barriers such as stock-outs, being asked for bribes and disrespectful treatment persisted. Conclusion The combination of expanding FSW-targeted SRH services with improving access to the public health services, resulted in an overall increased uptake of services, but almost exclusively because of the strengthened targeted (vertical) outreach services. Utilization of public SRH services had not yet increased and many barriers to access remained. Our diagonal approach was thus only successful in its vertical component. Improving access to the general health services remains nevertheless important and further research is needed how to reduce barriers. Ideally, the combination approach should be maintained and more successful approaches to increase utilization of public services should be explored.